Krytyka refleksywna w badaniach nad praktyką zawodową i organizacyjną - Nowak-Posadzy, Krzysztof (Wydawnictwo Naukowe UAM, 2014)
This article attempts to show that certain modes of checking practitioners’ and an organization’s knowledge (as analyzed by means of professional practitioner research), can be seen as stemming from general philosophical notions of critique. The term “critique” has been interpreted in many different ways, depending on the philosophical tradition, and has been operationalized in various ways, according to the methodological standards in a given branch of science or field of research. Critique can thus be legitimately defined in terms of (1) reflection, (2) negation, or (3) revision and it can have (1) neutral, (2) negative, or (3) positive implications. Practitioner research (PR), among other objectives, investigates numerous professionals’ (or organizations’) modes of learning that are necessary to make their work (or functioning) more efficient. These types of learning can be considered in terms of (1) learning-by-doing from experience, (2) trial-and-error dealing with information, or (3) correction-and-revision of a given standard. In the first section of the paper the author wonders what kind of research PR is. In the second section he discusses three conceptual shifts in PR, which resulted in focusing on three ways of enhancing professional (organizational) knowledge (i.e. reflective practice, informational literacy, and an internal audit). Finally, the third section elaborates on the reflexive interpretation of critique in order to show that a philosophical approach to critique can be useful in grasping some of the practices (i.e. critical reflection) that have occurred in professional and organizational reality and deserve methodological attention.
Reflexive Critique in Professional Practitioner Research
Keywords: critique; criticism; critical thinking; practitioner research; critical reflection; information criticism; professional skepticism